Staged seduction selling dreams in a Tokyo host club - Takeyama, Akiko 1970- (Stanford University Press, 2016)
This manuscript provides a window into the Japanese nighttime bars where male hosts seduce their female clients and entice them to spend money. It attempts to answer questions such as: what happens when women are the financial providers and men are the paid seducers? How do they communicate when women want to be seduced but cannot say so? What is it like to be in a commodified form of romance? Takeyama investigates various aspects of the host clubs including the host club as workplace, the hosts themselves, the women who frequent host clubs, the club managers, and the ethics of host club deception. Ultimately, the book provides readers with an extraordinary look into the dynamics of seduction, and the broader dynamics of the contemporary Japanese political economy.--Publisher's description